Monitoring indicators of economic activities in Sudan amidst ongoing conflict using satellite data - Guo, Zhe; Abushama, Hala; Siddig, Khalid; Kirui, Oliver K.; Abay, Kibrom A.; You, Liangzhi (Informa UK Limited, 2024)
Political tensions in Sudan between the Sudanese Armed Forces (SAF) and Rapid Support Forces (RSF) escalated into an armed conflict on 15 April 2023, and continues to unfold to date. Besides the severe humanitarian catastrophe, the war disrupted access to basic public services and constrained access to markets and continued to trigger considerable scarcity of life-saving goods and services. In this paper, we utilize satellite data (nitrogen dioxide (NO2) concentration and nightlight intensity) and spatial mapping tools to provide a swift analysis of how the conflict has changed the patterns on economic activity, which are bound to have severe implications on food security in Sudan. We show that immediately after the outbreak of the armed conflict, NO2 concentration and nightlight intensity reduced in those areas affected by the conflict while remaining stable in those areas not directly affected by the conflict. We also demonstrate how these types of remote sensing and remote data collection methods can be deployed to monitor economic activities amidst armed conflicts and similar abrupt crises and guide economic, development and environmental policies.